Miniaturized metalloproteins: Application to iron–sulfur proteins - Lombardi, Angela (The National Academy of Sciences, 2000)
The miniaturization process applied to rubredoxins generated a class of peptide-based metalloprotein models, named METP (miniaturized electron transfer protein). The crystal structure of Desulfovibrio vulgaris rubredoxin was selected as a template for the construction of a tetrahedral (S(γ)-Cys)(4) iron-binding site. Analysis of the structure showed that a sphere of 17 Å in diameter, centered on the metal, circumscribes two unconnected approximately C(2) symmetry related β-hairpins, each containing the -Cys-(Aaa)(2)-Cys- sequence. These observations provided a starting point for the design of an undecapeptide, which self assembles in the presence of tetrahedrally coordinating metal ions. The METP peptide was synthesized in good yield by standard methodologies. Successful assembly of the METP peptide with Co(II), Zn(II), Fe(II/III), in the expected 2:1 stoichiometry, was proven by UV-visible and circular dichroism spectroscopies. UV-visible analysis of the metal complexes indicated the four Cys ligands tetrahedrally arrange around the metal ion, as designed. Circular dichroism measurements on both the free and metal-bound forms revealed that the metal coordination drives the peptide chain to fold into a turned conformation. NMR characterization of the Zn(II)-METP complex fully supported the structure of the designed model. These results prove that METP reproduces the main features of rubredoxin.